Salicylic acid on induction of disease resistance in cucumber and control of Pythium sp. in vitro (Revista de Ciências Agroveterinárias, 2015)
The objective of this study was to evaluate the effect of salicylic acid concentrations (SA) in the induction of resistance of tipping cucumber seedlings and in vitro control of Pythium sp. The treatment of cucumber seeds was carried out using SA soaking solution for 5 min at concentrations of 0 (distilled water), 0.5, 1.0, 1.5, and 2.0 mM. They were then sown in trays containing Plantmax Florestal® substrate sterilized and inoculated with Pythium sp. The experiment was conducted for 14 days in a growth chamber with controlled temperature (23 °C ± 2 °C), light (photoperiod of 12 hours) and relative humidity (70% ± 10%). We evaluated the percentage of seedling emergence, percentage of tipping, seedling length, and fresh weight. The levels of the enzymes phenylalanine ammonia lyase (PAL), β-1,3-glucanase and chitinase were also quantified. In the experiment in vitro, SA was incorporated into the PDA (Potato, Dextrose and Agar) and we measured the mycelial growth of Pythium sp. The treatment of cucumber seeds with concentrations above 1 mM SA reduces the incidence of seedling damping-off caused by Pythium sp., however, it was not possible to discover enzymes related to the induction of resistance. The SA has no effect on the mycelial growth of Pythium sp. in vitro.
Keywords: Cucumis sativus L.; elicitor; inducing resistance; damping-off.